Marketing Management in the Sphere of Hotel and Tourist Services - Goryushkina, Natalia Ye.; Shkurkin, Dmitry V.; Petrenko, Antonina S.; Demin, Sergey Y.; Yarovaya, Natalia S. (International Review of Management and Marketing, 2016)
The relevance of marketing activity management study in the hotel and tourism business organizations is urgent due to increased competition for customers among the organizations of the industry and the tourism industry in general. Deepening competition among hotels hotel industry leads to the fact that the object of the competition is not only on accommodation rates, but also new kinds of proposals to stimulate and motivate consumers, quality, variety of programs to encourage repeat customers’ discounts, bonuses, etc. This action leads to the following actions, which greatly increases the importance of marketing research the hospitality industry, allowing identifying trends and areas for further development, management policy, and implementation of key performance indicators of the complex as a whole. Therefore, before each of the domestic hotel, a global hotel business there is a problem of search marketing management techniques that would strengthen a long time, and ensure its own stable position in the competition for the customer. Policy management marketing business hotel and tourist business of the country, the world’s states and territories of the resort specialization in their methodology defines essential for efficient operation of a hotel-tourist complex full satisfaction of the needs of consumers of travel services, which suggests them in the necessary production and sales volume, range and quality required with the application of marketing concepts. Keywords: marketing, services, management, competition, innovation JEL Classifications: M31, M10, M12